Foot and Mouth Disease Impact on Milk Productivity and Quality in KUD Kertajaya, Kediri, Indonesia - Oktanella, Yudit; Cahyani, Ayunda Ageng; Hendrawan, Viski Fitri; Nugroho, Widi; Agustina, Galuh Chandra (Universitas Airlangga, 2023)
One of the impacts of foot and mouth disease (FMD) on the dairy farming sector is decreasing the quantity and quality of milk production. This study aimed to determine the impact of FMD by observing the productivity and quality of fresh milk during FMD outbreaks. Sampling was performed to obtain productivity data before and during the FMD outbreak using the cluster sampling method in five areas in KUD Kertajaya, Kediri, Indonesia. The lactoscan test was used to analyze the quality of fresh milk from 50 positive samples. Based on the statistical analysis using the paired parametric T-test, it was reported that there was a significant difference in milk productivity before and during the FMD outbreak (p < 0,05). The results of the Lactoscan test on 50 positive samples showed an average fat content of 4,43%, solid nonfat (SNF) content of 8,54%, specific gravity of 1,028, lactose content of 4,67%, total solids content of 12,97%, added water content of 1,44 and freezing point of -0,54°C. In conclusion, the milk of dairy cows during the FMD outbreak often displayed a quality value of milk that met SNI requirements, despite the fact that there was a major decline in productivity.